[K.0.3] Ni sekobirikea ni sekobirikia: sekobiriza. A propósito del tratamiento *g-yod en celtibérico (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The authors present not only linguistic, but also paleo-epigraphic evidences in favor of the reading sekobiriza in [K.0.3].